IMF Data Standards Initiatives : A Consultative Approach To Enhancing Global Data Transparency - Kester, Anne. (Washington, D.C. : International Monetary Fund, 2006)
Since the IMF launched the data standards initiatives a decade ago, 145 of its 184 member countries have participated. This 80 percent participation rate reaffirms the importance countries place on data transparency in the globalized economy, which the initiatives promote. The wide participation can be attributed to the consultative process that has allowed for the development of a coherent program that takes account of countries' capabilities, delineates clear responsibilities between the IMF and participating countries, and establishes effective monitoring procedures to ensure the credibility of the standards for policymakers, capital markets, and the general public. The approach has also provided checks and balances and fostered accountability. The initiatives may provide insights for the promotion of similar international standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Singapore